Premedication practices for tracheal intubation in neonates transported by French medical transport teams: a prospective observational study. Issue 11 (14th November 2019) - Carbajal, Ricardo; Lode, Noella; Ayachi, Azzedine; Chouakri, Ourida; Henry-Larzul, Véronique; Kessous, Katia; Normand, Audrey; Courtois, Emilie; Rousseau, Jessica; Cimerman, Patricia; Chabernaud, Jean-Louis
Abstract : Objectives: Premedication practices for neonatal tracheal intubations have not yet been described for neonatal transport teams. Our objective is to describe the use of sedation/analgesia (SA) for tracheal intubations and to assess its tolerance in neonates transported by medical transport teams in France. Setting: This prospective observational study was part of the EPIPPAIN 2 project and collected around-the-clock data on SA practices in neonates intubated by all five paediatric medical transport teams of the Paris region during a 2-month period. Intubations were classified as emergent, semiemergent and non-emergent. Sedation level and conditions of intubation were assessed with the T onus, R eactivity, A wareness and C onditions of intubation to H elp in E ndotracheal intubation A ssessment (TRACHEA score). The scores range from 0 to 10 representing an increasing ladder from adequate to inadequate sedation, and from excellent to very poor conditions of intubation. Participants: 40 neonates intubated in 28 different centres. Results: The mean (SD) age was 34.9 (3.9) weeks, and 62.5% were intubated in the delivery room. 30/40 (75%) of intubations were performed with the use of SA. In 18/30 (60.0%) intubations performed with SA, the drug regimen was the association of sufentanil and midazolam. Atropine was given in 19/40 intubations. From the 16, 21 and 3 intubations classified as emergent, semiemergent and non-emergent, respectively, 8 (50%), 19 (90.5%) and 3 (100%) were performed with SA premedication. 79.3% of intubations performed with SA had TRACHEA scores of 3 or less. 22/40 (55%) infants had at least one of the following adverse events: muscle rigidity, bradycardia below 100/min, desaturation below 80% and nose or pharynx–larynx bleeding. 7/24 (29.2%) of those who had only one attempt presented at least one of these adverse events compared with 15/16 (93.8%) of those who needed two or more attempts (p<0.001). Conclusion: SA premedication is largely feasible for tracheal intubations performed in neonates transported by medical transport teams including intubations judged as emergent or semiemergent. Trial registration number: NCT01346813 ; Results.